Patton - Coppola, Francis Ford 1939-; North, Edmund H.; Bradley, Omar Nelson 1893-1981; Scott, George C. 1927-1999; Malden, Karl
Story of General Patton in World War II whose military brilliance was balanced by his inability to deal with the social and political aspects of war, causing him difficulties in his dealings with the War Department.